Circulating Immune Complex in Glomerular Diseases - Alatas, H.; Wirya, I. G. N. Wila; Tambunan, Taralan; Cornain, S.; Sucahyo, Sucahyo; Himawan, S.; Gunardjono, Gunardjono (Paediatrica Indonesiana, 1982)
Circulating Immune Complex (CIC) in the serum have been studied in 75 patients with glomerular diseases. The highest positive rate in patients with post streptococcal glomerulonephritis and lupus nephritis were respectively 83.3% atld 75%. In nephrotic syndrome: 33.3% (5 jl5) was positive in diffuse mesangial proliferative cases, and in all 3 patient Â· with membranoproliferative glomerulonephritis, membranous nephropathy and focalÂ glomerulosclerosis. All of them had detectable immune deposits in the glomeruli. In minimal lesion nephrotic syndrome (MLNS) without glomerular immune deposits, CIC was positive in 2 out of 17 cases (12%). This support the hypothesis that in MLNS a humoral immune mechanil’im might take part in the pathogenesis of the disease.